FIRST EVIDENCE OF THE SORICIDAE (MAMMALIA) ASORICULUS GIBBERODON (PETÉNYI, 1864) IN THE PLEISTOCENE OF NORTH IBERIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The paper describes thirteen specimens of the extinct red-toothed shrew Asoriculus gibberodon (Petényi, 1864) from the lower levels (8 to 14) of the Sima del Elefante cave (TE Lower Red Unit). These are the first bona fide examples of this taxon in the north of the Iberian peninsula. The Lower Red Unit of the Sima del Elefante dates from the early Pleistocene and contains evidence of the very first human activity in the European continent, in the form of lithic tools and large mammal bones with cutmarks.After a detailed discussion of systematic considerations, we focus on the palaeoecological and palaeobiogeographical implications of the presence of this species in the Sima del Elefante¡¦s Lower Red Unit. In palaeoecological terms, as a member of the Neomyini, A. gibberodon would have had a mainly aquatic life and is taken as an indicator of humid environments with a permanent green covering. As for its palaeobiogeographical implications, on the basis of its geographical distribution and morphometric particularities we have reconstructed the biogeography of the genus Asoriculus from its very first record at the end of the Miocene to its extinction shortly before the beginning of the middle Pleistocene.